Holiday effect on the Singapore stock market : behavioural or market-driven? - Gan, Jia Hao (2013)
Substantial past studies have shown the presence of holiday effect in the Singapore stock market. This paper re-examines the holiday effect in the recent years from 1993 to 2012. Its main objectives are to determine the presence of the holiday effect, the effect of the various cultural and state holidays on the Singapore stock market and the interaction between financial crises and the holiday effect.